Антикризове управління підприємством в умовах війни: загальна характеристика й пошук рішень щодо доцільності його запровадження - Кривов’язюк, Ігор Володимирович (Одеса : Гельветика, 2025)
В статті розкрито загальну характеристику та методичні засади вивчення доцільності запровадження антикризового управління підприємством в умовах війни. Проаналізовано наукові підходи учених сучасності щодо тлумачення сутності поняття «антикризове управління підприємством», за результатами виокремлення переваг і недоліків яких запропоновано його авторське трактування. Узагальнено сутнісну характеристику антикризового управління підприємством в умовах війни шляхом взаємоузгодження факторів, що впливають на ефективність його реалізації, потенційних результатів, стратегічних і тактичних цілей та різновидів антикризового управління. Запропоновано методику пошуку рішень щодо запровадження антикризового управління підприємством в умовах війни, що сприятиме формуванню баз даних для розкриття управлінської ситуації на підприємстві та подальшого прийняття на цій основі обгрунтованих антикризових рішень.

The main goal of the study is to deepen the theoretical and methodological foundations for the introduction of anti-crisis management of the enterprise in conditions of war. The relevance of the topic is determined by the need to ensure the viability of enterprises in a situation of uncertainty, constant risks and large-scale destruction of production and logistics infrastructure. The methodological basis of the work is based on a system of applied research methods: when carrying out a critical analysis of scientists' approaches to defining the essence of the concept of «anti-crisis management of the enterprise» – methods of induction and theoretical generalization; to generalize the essential characteristics of anti-crisis management of the enterprise in wartime conditions – methods of cause-and-effect relationship and grouping; to improve the methodological principles of diagnosing the expediency of introducing anti-crisis management of the enterprise in wartime conditions – methods of comparison and synthesis; for formulating conclusions and developing recommendations – logical generalization. On the basis of a critical analysis of the scientific approaches of modern scientists to defining the essence of the concept of «anti-crisis management of the enterprise», a new term is proposed, which is identified with management aimed at preventing, minimizing or avoiding the negative impact of crises in the enterprise's activities as a result of waging war in the country by predicting their occurrence with the help of specialized diagnostic tools and minimizing their destructive impact thanks to the preventive implementation of anti-crisis measures. The generalization of the essential characteristics of the anti-crisis management of the enterprise in the conditions of war was carried out by mutual coordination of factors affecting the effectiveness of its implementation, potential results, strategic and tactical goals and types of anti-crisis management. The proposed method of finding solutions regarding the expediency of introducing anti-crisis management of the enterprise in wartime conditions (which provides for a clear definition of the criteria of such expediency, priorities of actions of enterprises in wartime conditions, taking into account various risks for business, development of typical scenarios and packages of anti-crisis decisions, plans for the implementation of actions) will contribute to the formation of databases for making well-founded anti-crisis decisions on this basis. The results of the research include the development of theoretical and methodological provisions that form the basis for the further synthesis of anti-crisis management and decision-making with the aim of further justified choice of anti-crisis decisions by enterprises in wartime conditions. This contributes to increasing the overall efficiency of enterprise management.
Anti-crisis management of the enterprise in the conditions of war: general characteristics and search for solutions regarding the expediency of its introduction
Keywords: криза; антикризове управління підприємством; діагностика; управлінські рішення; ризики; війна